Introduction: Heteroglossia, performance, power, and participation. (23rd April 2015) - Jaffe, Alexandra; Koven, Michèle; Perrino, Sabina; Vigouroux, Cécile B.; Jaffe, Alexandra; Koven, Michèle; Perrino, Sabina; Vigouroux, Cécile B.
<x content-type="archive" xml:space="preserve">Abstract</x> In this special issue, we build on Bauman's seminal observation about performance, that 'the act of expression is put on display, objectified, marked out to a degree from its discursive surrounding and opened up to interpretive scrutiny and evaluation by an audience' (2000:1). More recently, scholars have moved to examining the performative role of heteroglossia, that is, the use of multiply sourced, semiotic (verbal and nonverbal) forms. In particular, this line of research has shown how attention to heteroglossic performances and their local interpretations can illuminate the subtle politics of dominant and nondominant identities in different ethnographic contexts. This is particularly true of what Coupland (2007) calls 'high performances', which, as Bell & Gibson (2011:558) write, are privileged sites for allowing participants to indexically associate expressive forms with social personae. Thus, while all performances are inherently reflexive, heteroglossic performances particularly amplify that reflexivity with respect to their multiple frames, voices, and stances that they presuppose and establish.